Comprehensive investigation of persistent and mobile chemicals and per- and polyfluoroalkyl substances in urine of flemish adolescents using a suspect screening approach. (1st November 2022) - Kim, Da-Hye; Jeong, Yunsun; Belova, Lidia; Roggeman, Maarten; Fernández, Sandra F.; Poma, Giulia; Remy, Sylvie; Verheyen, Veerle J.; Schoeters, Greet; van Nuijs, Alexander L.N.; Covaci, Adrian
Abstract: Persistent and mobile chemicals (PMs) and per- and polyfluoroalkyl substances (PFAS) are groups of chemicals that have received recent global attention due to their potential health effects on the environment and humans. In this study, exposure to a broad range of PMs and PFAS was investigated in Flemish adolescents' urine samples ( n  = 83) using a suspect screening approach. For this purpose, three sample preparation methods were evaluated, and a basic liquid-liquid extraction was optimized for urine analysis based on the extraction efficiency of PMs (53–80%) and PFAS (>70%). In total, 9 PMs were identified in urine samples at confidence levels (CL) 1–3 and, among them, acetaminophen, 4-aminophenol, 2, 2, 6, 6-tetramethyl-4-piperidone, trifluoroacetic acid (TFAA), sulisobenzone, ethyl sulfate, and 1, 2-benzisothiazol-3(2H)-one 1, 1-dioxide were confirmed at CL 1 and 2. In addition, the detection and identification of 2, 2, 6, 6-tetramethyl-4-piperidone, 4-aminophenol, TFAA, and m-(2, 3-epoxypropoxy)-N, N-bis(2, 3-epoxypropyl) aniline (CL 3), has been reported for the first time in human urine in this study. For PFAS, only 2 compounds were identified at CL 4, implying that urine is not a suitable matrix for suspect screening of such compounds. A significant difference between sexes was observed in the detection rate of identified PMs, in particular for acetaminophen, 4-aminophenol, and sulisobenzone. The findings of this study can be used in future human biomonitoring programs, such as by including the newly identified compounds in quantitative methods or monitoring in other human matrices (e.g., serum). Graphical abstract: Image 1 Highlights: PMs and PFAS in urine from Flemish adolescents were assessed by suspect screening. Sample preparation was optimized for simultaneous analysis of PMs and PFAS in urine. PMs and 2 PFAS were identified in urine samples at confidence levels 1 to 4. Detection rate of PMs in female urine was significantly higher than in males.